PENGUKURAN DALAM PENELITIAN PSIKOLOGI - Rosleny Marliani (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2010)
Psychology is the science of human and animal behavior. It is also intended to get a clear description of any evidence or behavior of any population. For example,we want to know the correlation of teenagers’ intelligence and their creativity. It is an example of such case that can be described and measured by using some indicators.Measurement in psychology is very important because it is not only an art but also a science. As science it is empirical. It is of course relies on experiment and observation, rather than argument, opinion or belief.Moreover, Morgan (1961) said that the progress of in science often depends upon the development of quantitative methods. Without such methods,science is limited to crude observation and classification. By using them we are able to refine data-based conclusions.There are so many kinds of measurement that can be used in psychological field, such as test, personality inventory,attitude scale,etc. There are some important aspect that should be noted in measurement, such as reliability and validity.